(3CSFdI GdbQBf hCLhHJgGs - (3eMeO Hf CHj HcQ Hf YHO GdbGOQ GdQGRj GdMfaj, Rjf GdOjf,J (B666 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdGeGe GdYGde eMeO Hf CHj HcQ Hf YHO GdbGOQ GdQGRi gPG eNJUQ LeYJ ajg GfehPLkG jSjQkG ef GSFdI GdbQBf GdeLjO hGLhHJgG s
(3BNQgG (B:s
(3aEf bjd cja bGd hGJjJe GMOGgf bfWGQkG GdBjg eY Gf s
(3HgG fXGe GdJYbjHIs
(3hgj Gda heGFJG SDGds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B55 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B112s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B92s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs